KOMUNIKASI KELUARGA - Sari, Etika; Herawati, Azizah (Jurnal Bimas Islam, 2017)
This study aims to find out the interpersonal communication process by married couples in the divorce process and how to solve the conflicts conducted by married couples in the divorce process. The data collection method of this research is qualitative approach, the technique is collecting the data by observating, with the deep interviewed. The research object in KUA Gamping sub-district, as the subject are four married couples. The result of this research demonstrated that interpersonal communication married couples process is biggining with a prejudice, one of them soundless to tell what problem that comes to their household such as debts and receivables even any other problem which is bad to conflict,  no open minded conversation to each other, their egos with the result that guesting she or he is the right one so every opinion really unacceptable for each other. Secondly, problem solving is found out of these married couples are win-lose solution and win-win solution. Win-win solution is applying if there a mediation married couples to help their problem by KUA Gamping counselor. Penelitian ini dilakukan bertujuan untuk mengetahui proses komunikasi interpersonal pada pasangan suami istri dalam proses cerai dan untuk mengetahui cara penyelesaian konflik yang dilakukan oleh pasangan suami istri dalam proses cerai. Metode penelitian ini menggunakan pendekatan kualitatif, dengan wawancara mendalam. Objek penelitian di KUA kecamatan Gamping, sebagai subjek adalah empat pasangan suami dan istri. Hasil penelitian ini menunjukan bahwa proses komunikasi interpersonal pada pasangan suami istri ini bermula pada prasangka, bungkamnya pasangan suami istri yang tidak di diskusikan setiap masalah baik hutang-piutang maupun masalah lain, tidak adanya dialog secara terbuka dan keegoisan pasangan yang merasa paling benar dan tidak mau saling menerima pendapat setiap pasangan. Penyelesaiaan yang dilakukan pada pasangan suami istri ini menemukan jalan win-lose solution dan win-win solution. Penyelesaian konflik yang berjalan secara win-win solution apabila dilakukannya mediasi sebagai penengah masalah pasangan yang dilakukan oleh penyuluh di KUA Gamping.